Republic of Estonia : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper analyzes income convergence and medium-term growth potential for Estonia. Estonia's potential growth is projected to average some 3 percent over the next five years and 2.75 percent over the next two decades, implying continued income convergence with European Union levels, albeit at only half its historical pace. A number of policy enhancements could lift growth above this central projection. These include a greater operational policy focus on raising productivity growth, scaling up a number of envisaged pro-growth programs, supporting the upgrading of traditional industries as a second leg of innovation policy, and fully restoring Estonia's high investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet